Reduced frontostriatal functional connectivity and associations with severity of Internet gaming disorder. (24th November 2020) - Dong, Haohao; Wang, Min; Zhang, Jialin; Hu, Yuzheng; Potenza, Marc N.; Dong, Guang‐Heng
Abstract: Cognitive, functional, and structural brain factors involving frontal executive and striatal reward networks have been implicated in Internet gaming disorder (IGD). However, frontostriatal network connectivity and its association with addiction severity are poorly understood in IGD. Resting‐state fMRI data from 337 subjects (130 with IGD, 207 with recreational game use [RGU]) were collected. Striatal‐cortical communications were measured with resting‐state functional connectivity (FC) using coherent spontaneous fluctuations in the blood‐oxygenation‐level–dependent fMRI signal. Correlations were calculated between FC measures and IGD‐related assessments (addiction severity and craving scores). Decreased FC was predominantly observed in IGD subjects, with IGD subjects showing decreased FC between the putamen and superior frontal gyrus (SFG), middle frontal gyrus (MFG), and inferior frontal gyrus (IFG) and the ventral striatum and IFG, superior temporal gyrus, and MFG. Disorder severity and craving scores were negatively correlated with FC between striatal and frontal brain regions. Associations between diminished FC in corticostriatal circuitry and clinical features (IGD craving, severity) suggest potential therapeutic targets for neuromodulation treatments. The extent to which frontostriatal circuits involving executive control over reward processes may be altered to treat IGD warrants additional study. Abstract : The current study collected resting‐state data from 337 subjects (130 IGD subjects and 207 with recreational game use). We took striatal regions as ROIs and examined their correlations with cortical brain regions. We observed significant decreased frontostriatal functional connectivity in IGD subjects, with specific frontal cortical brain regions thus representing potential targets for neuromodulation interventions.